Retinoic acid: a key regulator of lung development - Fernandes-Silva, Hugo (2020)
Retinoic acid (RA) is a key molecular player in embryogenesis and adult tissue homeostasis. In embryo development, RA plays a crucial role in the formation of different organ systems, namely, the respiratory system. During lung development, there is a spatiotemporal regulation of RA levels that assures the formation of a fully functional organ. RA signaling influences lung specification, branching morphogenesis, and alveolarization by regulating the expression of particular target genes. Moreover, cooperation with other developmental pathways is essential to shape lung organogenesis. This review focuses on the events regulated by retinoic acid during lung developmental phases and pulmonary vascular development; also, it aims to provide a snapshot of RA interplay with other well-known regulators of lung development.